El juego como estrategia motivacional en el proceso de enseñanza-aprendizaje de los niños y niñas del primer año de las escuelas de educación básica 24 de Junio y Presidente Jaime Roldós Aguilera, de la ciudad de Machala, en el periodo lectivo 2012-2013. - González Ramón, Evelyn Marina (2014)
The development of this thesis: The game as a motivational strategy in the process of teaching and learning of children in the first year of basic education schools on June 24 and President Jaime Roldós Aguilera, of the city of Machala, in the academic year 2012-2013, is a proactive diagnostic research work aimed at determining how often the game is used as a motivational strategy in the process of teaching and learning of children in the first year of basic education schools for which a methodological process based on inductive, deductive, descriptive, and the hypothetical statistical methods, which relied on techniques, observation, interviews, surveys and signing took place.